PSEN1 c.1292C<A Variant and Early-Onset Alzheimer’s Disease: A Scoping Review - Orozco-Barajas, Maribel; Oropeza-Ruvalcaba, Yulisa; Canales-Aguirre, Alejandro A.; Sánchez-González, Victor J. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common cause of dementia, characterized by progressive loss of cognitive function, with β-amyloid plaques and neurofibrillary tangles being its major pathological findings. Although the disease mainly affects the elderly, c. 5–10% of the cases are due to PSEN1, PSEN2, and APP mutations, principally associated with an early onset of the disease. The A413E (rs63750083) PSEN1 variant, identified in 2001, is associated with early-onset Alzheimer’s disease (EOAD). Although there is scant knowledge about the disease’s clinical manifestations and particular features, significant clinical heterogeneity was reported, with a high incidence of spastic paraparesis (SP), language impairments, and psychiatric and motor manifestations. This scoping review aims to synthesize findings related to the A431E variant of PSEN1. In the search, we followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and the guidelines proposed by Arksey and O’Malley. We searched and identified 247 studies including the A431E variant of PSEN1 from 2001 to 2021 in five databases and one search engine. After the removal of duplicates, and apply inclusion criteria, 42 studies were finally included. We considered a narrative synthesis with a qualitative approach for the analysis of the data. Given the study sample conformation, we divided the results into those carried out only with participants carrying A431E (seven studies), subjects with PSEN variants (11 studies), and variants associated with EOAD in PSEN1, PSEN2, and APP (24 studies). The resulting synthesis indicates most studies involve Mexican and Mexican-American participants in preclinical stages. The articles analyzed included carrier characteristics in categories such as genetics, clinical, imaging techniques, neuropsychology, neuropathology, and biomarkers. Some studies also considered family members’ beliefs and caregivers’ experiences. Heterogeneity in both the studies found and carrier samples of EOAD-related gene variants does not allow for the generalization of the findings. Future research should focus on reporting data on the progression of carrier characteristics through time and reporting results independently or comparing them across variants.